ANALISIS TEOLOGIS HUBUNGAN KESEHATAN TUBUH DENGAN KESELAMATAN BERDASARKAN 1 TESALONIKA 5:23 - Pierson Parapat; Milton T. Pardosi (Fakultas Filsafat Universitas Advent Indonesia, 2018)
The term “qadash” is derived from the root word qad which its basic definition is “tocut off” the use of this term in a religious perspective pointing to the meaning of “theseparation that connects with God to a special position, which is union orcommunion with Him.”Man is a sinful creature and full of shortcomings, only God is perfect and neverwrong. In Greek, the original language of the New Testament, the word perfect isteleios, which also means purpose. If that purpose has been reached, the teleiosbecomes perfect. In other words, for the Greeks, perfection means functioning.The translated word “without blemish” is amomos in Greek which describes how aChristian looks like before God. It corresponds to the animal sacrifices that areworthy to be sacrificed to God. The Christian life must be as such that it can beoffered as the blameless animal sacrifice to God.